Production of ornamental pepper on different substrates and pot sizes (Research, Society and Development, 2024)
Floriculture stands as a significant contributor to job creation and income generation in Brazil. In this context, ornamental pepper cultivars emerge as a compelling option due to their versatility in being cultivated and marketed in pots. Within this framework, the objective was to assess the impact of different substrates and pot sizes on the production of potted ornamental pepper plants in Chapecó-SC. The experiment was conducted in a greenhouse, employing a randomized block design in a 3x3 factorial scheme (pot sizes and substrate types), with 4 replications. Seeds of the Stromboli cultivar and three pot sizes were utilized: N° 13 (725 mL), N° 14 (1 L), and N° 15 (1.16L). The substrates employed were Carolina Soil®, Mecplant® and Garden Plus®. Assessments encompassed plant height, number of leaves per plant, stem diameter, leaf area, number of fruits per plant, fruit size, dry plant mass, and ornamental quality. The obtained results underwent analysis of variance, and mean comparisons were conducted through the Tukey test (p